Gallbladder Carcinomas: An Immunoprognostic Evaluation of P53; Bcl-2; CEA and Alpha-Fetoprotein - R Kanthan; JM Radhi; SC Kanthan (Canadian Journal of Gastroenterology)
The p53 gene is the most frequently mutated gene in many human cancers, including those of the colon, breast, lung, esophagus, liver and brain. Such genetically mutated tumours are generally associated with progression of the disease and poor clinical outcome. One hundred cases of documented gallbladder carcinomas were reviewed. Twenty-eight cases were randomly selected to evaluate the expression of P53, Bcl-2, carcinoembryonic antigen (CEA) and alpha-fetoprotein, in both the in situ (19 cases) and invasive components (28 cases) of the tumour by the avidin-biotin complex method of immunohistochemistry. These results were correlated with the mean survival intervals in an effort to clarify the progression of the disease and evaluate their role as prognostic markers. Staining to alpha-fetoprotein and Bcl-2 remained consistently negative to weak insignificant staining in both the in situ and invasive components of the tumour in all cases. P53 staining of the invasive part of the tumour was seen in 24 (86%) of the cases and in 17 (89%) of the in situ component. The in situ staining patterns of P53 were not statistically significant in relation to the mean survival. However, in the invasive component, moderate to strong staining tumours, as seen in 15 (54%) cases, were associated with a mean survival of 8.8 months. A similar trend was also observed with staining patterns to CEA. Eighty-nine per cent of the invasive and 84% of the in situ components of the tumour stained positive to CEA. Moderate to strong staining of both the in situ and the invasive components of the tumours was associated with a mean survival of 10.6 months in 76% of cases. This study shows that altered expressions of P53 and CEA are detectable by immunohistochemistry in gallbladder carcinomas. Tumours with increased expression of P53 and CEA of a strong to moderate staining were associated with poor clinical outcomes as evidenced by their mean survival. A stepwise progression of altered CEA and P53 expression may reflect ongoing progression of the disease from the in situ to the invasive phase. However, such trends need to be evaluated in larger numbers and are thus not considered to be true independent prognostic markers.